Pemanfaatann Arduino Uno pada Eksperimental Oil Leakage Detector Piston Engine Lycoming O-360 - Imam Syafi'i; wira gauthama; Sihono Sihono (Politeknik Penerbangan Indonesia Curug, 2022)
One of the systems on the aircraft is the lubrication system. This system is very prone to problems, one of which is oil leakage, where the risk is hazardous if this condition is ignored, including the wear on moving parts that can occur such as in the gearbox and bearings so that engine performance can become abnormal and even result in accidents. This research objective was to develop an oil leak detector on the Lycoming O-360 engine based on the Arduino Uno. With the development of current microcontroller technology, the tool's design was made into an experimental tool used to detect oil leaks using a microcontroller. The research method uses the design method by Pahl and Beitz, which consists of four stages in a design: planning and analysis, concept design, form design, and detail design. The design research results are acrylic with a maximum temperature resistance of 88°C as a reservoir. As for the characteristics of the oil used in the Lycoming O-360 is grade SAE 50. The integrated components used include: Arduino UNO color sensor TCS3200, non-contact liquid sensor XKC-Y25, LCD 1602, I2C module, LED lights (red, yellow, green), buzzer, 6600 mAh battery, jumper cable, and 220 Ω resistor. The research concludes that the design of an Arduino UNO-based oil leak detector can run well and detect oil leakage.